2013
DOI: 10.1007/s00395-013-0399-0
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of Sirt3 does not affect atherosclerosis but accelerates weight gain and impairs rapid metabolic adaptation in LDL receptor knockout mice: implications for cardiovascular risk factor development

Abstract: Sirt3 is a mitochondrial NAD+-dependent deacetylase that governs mitochondrial metabolism and reactive oxygen species homeostasis. Sirt3 deficiency has been reported to accelerate the development of the metabolic syndrome. However, the role of Sirt3 in atherosclerosis remains enigmatic. We aimed to investigate whether Sirt3 deficiency affects atherosclerosis, plaque vulnerability, and metabolic homeostasis. Low-density lipoprotein receptor knockout (LDLR−/−) and LDLR/Sirt3 double-knockout (Sirt3−/−LDLR−/−) mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 44 publications
0
40
0
Order By: Relevance
“…Sirt3 appears dispensable in a number of other in vivo processes 25‐26,47 . One study showed that loss of Sirt3 had no identifiable effect on innate immune responses and host defense against bacterial and fungal infections 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Sirt3 appears dispensable in a number of other in vivo processes 25‐26,47 . One study showed that loss of Sirt3 had no identifiable effect on innate immune responses and host defense against bacterial and fungal infections 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, loss of SIRT3 promoted hyperacetylation of mitochondrial proteins, resulting in metabolic perturbations and increased susceptibility to metabolic disease 31 . Additionally, SIRT3 was demonstrated to regulate systemic oxidative stress, limit expedited weight gain, and promote metabolic adaptation 32 . Thus, animal studies suggest that SIRTs may protect against the development of metabolic disease.…”
Section: Potential Role Of Hdacs In Metabolic Diseasementioning
confidence: 99%
“…) mice results in increases in body weight, plasma glucose level and systemic oxidative stress, but does not accelerate the vascular oxidative stress or the development of atherosclerosis [115]. These findings suggest a potential role of SIRT3 in the development of cardiovascular risk factors and a function of postponing the onset of distinct metabolic risk factors.…”
Section: Sirt3mentioning
confidence: 70%
“…Therefore, it is possible that the activation of SOD in aorta under CR is also obtained through the activation of SIRT3. Although deletion of SIRT3 in LDLR  mice does not result in any exacerbation of vascular oxidative stress [115], we should not rule out the possibility that SIRT3 could regulate vascular oxidative stress under other circumstances. Compared with SIRT1 and SIRT3, other sirtuins, which also sense NAD + /NADH levels, are involved in the regulation of metabolism as well [123,124].…”
Section: Sirt3mentioning
confidence: 99%